Canine aggression to people. - Alfieri, Arsenio (Centro de Publicaciones Periódicas Electrónicas de la Universidad Nacional de Rosario, 2010)
Development and urbanization have brought about various changes and modalities in man/animal relationship. The interest in the study of this new relationship and its consequences is growing. . A descriptive epidemiological study of people with canine bite injuries was carried out from 2006 to 2008 in Arequito, Santa Fe, Argentina. A hundred and five injured people were interviewed -67% were adults, 21% children and 12% teenagers. Eighty-four percent of the lesions were located in the limbs, especially the lower ones (67%). The most common sites of attacks were public, 75%, and 46% of the attacks were caused by known dogs. Sixty-seven percent of biters were male. Aggressions were mostly from adult animals (83%), in general through chase associated with predation (48%). Thirty-six percent of animals had history of attacks to people. A typical victim is an adult male with lesions in lower limbs caused in streets by adult, medium-size male mongrels. No fatal victims were recorded but the severity of attacks was established by those children with facial lesions that required suture.
Received: May 2010 - Accepted: August 2010